Gamelets Providing diegetic elements through injection into digital children's books - Antonsson, Marcus (My University, 2013)
Tablets and smart phones using touch interfaces are becoming more and more common. New ideas and applications are brought to life every day, making daily use of computers more ubiquitous. With this new technology comes the possibility to read not only the news, but to read literature in new ways. The possibility with hypermedia means that narratives can be told using not only the text, but also with animation and interactable computer graphics and sound. In this thesis the idea of using gamelets are discussed. Gamelets are interactions and smaller games used within digital books in order to support the diegesis and add to the experience provided by a book. Several proof of concept prototypes was designed and implemented in order to analyze and create suggestions on what to consider when designing for an already existing narrative. These suggestions that can help utilize the modern technology in order to affect(or not affect) the existing narrative.
Keywords: Data- och informationsvetenskap; Computer and Information Science